SOME QUESTIONS OF MODALITY IN MODERN ENGLISH - Isayeva , Aygun (Collection of scientific papers «ΛΌГOΣ», 2025)
According to Huffman (1996), people use language as a means of communicating with each other and expressing their desires, emotions, thoughts, attitudes and needs. Communication is formed by people everywhere and at any time. However, although people constantly practice communication, misunderstandings still happen all the time, especially when people have different cultures. Communication between people is always influenced by differences in culture, including background, communication habits and languages, and all these factors cause misunderstandings. Unfortunately, misunderstandings are common - the listener or reader sometimes does not understand what is said or written. Before writing, people used pictures (cave paintings) that turned into verbal symbols. When people are going to speak or write, they shape their thoughts in such a way that they fit the context or situation. But in reality, the desires do not match the result. The meaning of words or sentences sometimes differs from the form of words.